Peranan Penyidik Dalam Menangani Tindak Pidana Perampasan Dengan Kekerasan Terhadap Pencurian Sepeda Motor (Studi Kasus Pada Polrestabes Medan) - Falentino Surya Situmorang; Rafiqi Rafiqi; Riswan Munthe (Universitas Medan Area, 2020)
The crime of seizure and theft of motorized vehicles with violence is so disturbing to the public. This research method was conducted using empirical juridical research methods. The role of the investigator is very important in overcoming the crime of seizure and theft of motorized vehicles with violence, bearing in mind the high number of crimes that occur in the community, especially in the surrounding area of the Medan City Police. The role of the Medan City Polrestabes in dealing with motor vehicle theft with violence appears from preventive and repressive efforts. As law enforcers, patrons and community guides through routine raids and patrols in places suspected of being prone to motor vehicle theft and socialization to the public. Inhibiting factors in the police, including the lack of witness participation in providing information in the investigation process, the limited number of investigators, inadequate income / salary factors of investigators, the lack of an investigative budget, inadequate facilities and infrastructure to support investigator performance and lack of participation witness in providing information in the investigation process.